Phase 1 LymfactinⓇ Study: Short-term Safety of Combined Adenoviral VEGF-C and Lymph Node Transfer Treatment for Upper Extremity Lymphedema - Pauliina Hartiala; Sinikka Suominen; Erkki Suominen; Ilkka Kaartinen; Juha Kiiski; Tiina Viitanen; Kari Alitalo; Anne M. Saarikko (Churchill Livingstone, 2022)
Objective: To study the safety and tolerability of LymfactinⓇ treatment combined with microvascular lymph node transfer surgery in patients with upper limb lymphedema.
Background: Upper limb lymphedema is a common clinical challenge after breast cancer surgery and/or radiotherapy. LymfactinⓇ is an adenovirus type 5–based gene therapy involving expression of human vascular endothelial growth factor C (VEGF-C) in the damaged tissue. It aims to correct deficient lymphatic flow by promoting the growth and repair of lymphatic vessels.
Methods: In Phase I, LymfactinⓇ was combined with microvascular lymph node transfer surgery to study the safety and tolerability of LymfactinⓇ and the biodistribution of the viral vector in patients with upper limb lymphedema.
Results: Fifteen patients with breast cancer–associated secondary lymphedema of the upper arm were recruited between December 2016 and February 2018. Three patients received a lower dose (1 × 1010) and 12 a higher dose (1 × 1011) of viral particles, respectively. No dose-limiting toxicities were observed, and the study was completed with the pre-determined maximum dose. Commonly reported adverse events during the 12-month follow-up were common cold, fever, gastroenteritis, pain in the operation area, headache, muscle ache and elevated liver enzymes. Serious adverse events consisted of two erysipelas infections in the lymphedema arm (requiring hospitalization) and one hematoma of the flap donor site.
Conclusions: After 12 months’ follow-up, results indicate that LymfactinⓇ is well tolerated. The study continues with a 36-months efficacy and 5 years safety follow-up of the patients. The oncological safety aspects of LymfactinⓇ will require a longer follow-up period.